Investigação empírica sobre o relacionamento entre Seis Sigma e prioridades competitivas - Silva, Brena Bezerra (2015)
Six Sigma is an improvement program adopted by many companies to improve their business performance. However, some studies indicate that the relationship between Six Sigma and competitive advantage is not that clear. In this context, the main objective of this dissertation is to identify the relationship between the implementation factors of Six Sigma and competitive priorities in companies that operating in Brazil. As steps, this research conducted bibliometric analysis, content analysis, descriptive analysis and factor analysis. The research investigated 45 companies, through a survey, to find the relationship between Six Sigma implementation factors with competitive priorities in Brazil. Implantation factors identified were: "collect and availability of data", "previous infrastructure", "performance indicators", "goal setting", "capacity for change", "top management involvement" and "statistical thinking" . The results indicate the implementation factors that have relationship with competitive priorities are "collection and availability of data," "previous infrastructure" and "capacity for change". In addition to this result, it was found that the dimensions of competitive priorities that have relationship with implementation factors are "reliability" and "flexibility".